The dynamics of integration and integrated care: An exploratory study of physician organizations. Issue 1 (27th January 2023) - Clark, Jonathan R.; Tietschert, Maike; Kerrissey, Michaela; Friedberg, Mark; Singer, Sara J.
Abstract : Background: Substantial variation exists in how well health care is integrated, even across similarly structured organizations, yet research about what physician organizations (POs) do that enables or inhibits integrated care is limited. Purpose: The aim of this study was to explore the dynamics that enable POs to integrate care. Methodology/Approach: We ranked a stratified sample of POs according to patient perceptions of integrated care, as measured in a survey. We interviewed professionals, patients, and family members in 10 higher and 3 lower ranked POs about the process of caring for patients with complex conditions. We derived integration-related themes from the interview data and quantified their prevalence. Using a quasi-statistical approach, we explored relationships among themes and their associations with patient perceptions of integrated care. Results: From 6, 104 coded references, we derived a set of themes representing integration perspectives, integration engagement mechanisms, and integration failures. POs experienced frequent integration failures. Higher ranked POs experienced these failures less often because of a combination of functional, interpersonal, and stakeholder engagement mechanisms, which appear to complement one another. Integration perspectives, including both people-oriented and systems-oriented mindsets, appear to play a role in generating these integration dynamics. Conclusion: Delivering integrated care depends on a PO's ability to limit integration failures, keeping provider attention focused on patients. Building on the attention-based view, we present a framework suggesting that this ability is a function of both integration perspectives and integration engagement mechanisms. Practice Implications: POs interested in delivering more integrated care should employ a variety of complementary integration engagement mechanisms and facilitate these efforts by nurturing both people-oriented and system-oriented mindsets among PO decision-makers.